CuO/CuBi2O4 bilayered heterojunction as an efficient photocathode for photoelectrochemical hydrogen evolution reaction. (23rd March 2021) - Zhang, Qing; Zhai, Bowen; Lin, Zheng; Zhao, Xinqing; Diao, Peng
Abstract: The poor photostability and low photoactivity are two bottlenecks limiting the application of CuO and CuBi2 O4 as competitive candidates for photoelectrochemical (PEC) hydrogen evolution reaction (HER). To overcome the bottlenecks, we constructed a novel CuO/CuBi2 O4 bilayered structure for PEC HER. The underlying CuO layer functions as the main photoabsorber, while the outside CuBi2 O4 layer acts as a protection shield. After further decorated with the NiOx electrocatalysts, the CuO/CuBi2 O4 /NiOx photocathode exhibits a high photoactivity and remarkable photostability. We ascribe this excellent performance to the following factors: (1) the bilayer structure improves light harvesting efficiency, (2) the outside CuBi2 O4 enhances the photostability, (3) the favorable band alignment increases charge separation efficiency, and (4) the presence of NiOx facilitates the charges transfer at the interface. Therefore, this work not only sets a new benchmark efficiency for the CuO and CuBi2 O4 heterojunction, but also provides principles for designing layered heterojunction for PEC water splitting. Graphical abstract: Image 1 Highlights: CuO/CuBi2 O4 bilayered composite is fabricated by a novel three-step method. Additional light harvesting is achieved when the composite is illuminated from backside. Constructing the CuO/CuBi2 O4 heterojunction promotes the separation of charges. The bilayered structure is beneficial to unidirectional charges transfer in PEC system. CuO/CuBi2 O4 /NiOx composite surpasses most of CuO catalysts in activity and stability.